TRANSFORMATION OF THE NATIONAL STATE IN THE CONDITIONS OF FORMATION OF NETWORK SOCIETY - Курочкін, Олександр В'ячеславович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article analyze the process of transformation of governance under new conditions of network society. The author examine the basic characteristics of network society and define the concept of governance as the most adequate theoretical foundation for public policy elaboration.